2017
DOI: 10.4314/sajas.v47i6.17
|View full text |Cite
|
Sign up to set email alerts
|

Potential of oak acorn with and without polyethylene glycol as an alternative to corn in broiler diets

Abstract: This study was conducted to investigate the potential for replacing corn with oak acorn (OA), a tanninrich feedstuff, and the possible role of polyethylene glycol (PEG) in reducing detrimental effects of OA on broilers. A 3 × 2 factorial arrangement of treatments was used with three levels of OA (0, 150, and 200 g/kg diet), with and without 10 g/kg PEG. A total of 528 one-day-old male and female Cobb 500 broiler chicks were randomly assigned to one of six experimental treatments, with four replicates of 22 bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
2
1
1
Order By: Relevance
“…Improved FCR in the hens fed 10% oak‐included diet is in agreement with the observations by Saeidi et al. (2017), who fed broiler oak‐included diet with or without polyethylene glycol. In a study conducted by Sharif et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Improved FCR in the hens fed 10% oak‐included diet is in agreement with the observations by Saeidi et al. (2017), who fed broiler oak‐included diet with or without polyethylene glycol. In a study conducted by Sharif et al.…”
Section: Discussionsupporting
confidence: 92%
“…is native tree in Iran (Zagross region) and annually large amounts of acorns (seed) are produced. This fruit contains high levels of starch (47%–60%) and 7%–14.4% lipids (Bouderoua et al., 2009), and due to its low price, it could be used as an alternative to corn in poultry diets (Bouderoua et al., 2009; Houshmand et al., 2015; Saeidi et al., 2017). Lipids of oak acorns contain linoleic acid and ω‐3 polyunsaturated fatty acid (Petrovic et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the present study is in agreement with the results obtained by Maidala et al [38], they found no significant differences in the body weight gain of broiler chicks fed a corn-based diet or those fed germinative sorghum-based diets. But the result of the present study does not agree with the results obtained by Saeidi et al [39], because their results indicated that dietary inclusion of oak (150 and 200 g/kg diet) significantly reduced body weight gain overall (days 1-42) and resulted in worse finishers and overall feed conversion ratios.…”
Section: Treatmentcontrasting
confidence: 99%
“…The result of the present study also indicated that treatment with different concentrations oak acorn flour had no significant influences on the liver and kidney weights if compared between each other or with the control group. This result was in agreement with the results of some investigators [8], which indicated that the tannin content of the oak acorn had no negative impact on the health of (Coturnix coturnix) Japanese quail [39], also reported that the liver and pancreas weights were not significantly influenced by the oak level (150 & 200 g/kg diet).…”
Section: Treatmentsupporting
confidence: 93%